Immunoprophylaxis of Children in Uzbekistan: Status and Prospects for Improvement - Shadmanov Alisher Kayumovich; Matnazarova Gulbahor Sultanovna; Tashmatova Gulnoza Aloevna; Durdiev Muzaffar (Scholars Digest Publishing, 2023)
The article presents the results of a retrospective analysis of the achievements of vaccination throughout the world and in our country. An assessment of the state of the vaccination business in the Republic of Uzbekistan was carried out. The necessity of expanding the National calendar of preventive vaccinations is substantiated. The main problems of vaccination prevention in the country are identified and proposed ways to solve them.
Keywords: vaccination, vaccine, safety and efficacy.